Climate Commitments: Analyzing the Application of ITMO in Indonesia-South Korea Bilateral Relations - Danuwijaya, Try; Ongom, Trevor Graham (Journal of Paradiplomacy and City Networks, 2025)
This study explores the evolving dynamics of climate diplomacy between Indonesia and South Korea through the lens of multitrack diplomacy and green political theory, focusing on the implementation of Internationally Transferred Mitigation Outcomes (ITMO) under Article 6 of the Paris Agreement. As global climate commitments increasingly rely on cooperative market-based mechanisms, bilateral partnerships have emerged as crucial pathways for achieving Nationally Determined Contributions (NDCs). Indonesia and South Korea have developed an ambitious climate collaboration agenda that not only involves traditional government-to-government (Track 1) engagement but also incorporates non-state actors, including research institutions, business sectors, and civil society organizations that operate across multiple tracks of diplomacy. This article investigates how these diverse actors advance the ITMO cooperation and contribute to strengthening bilateral environmental relations. Drawing on secondary data and document analysis, this paper illustrates how the synergy between tracks creates an enabling environment for technology transfer, capacity building, and joint carbon-offset projects, positioning ITMOs as both a diplomatic instrument and a climate policy tool. Although the partnership is promising, challenges remain in harmonizing regulatory frameworks. The findings highlight the necessity of a comprehensive Multitrack Diplomacy approach to maximize cross-sectoral engagement in ITMO implementation, especially on a bilateral basis.